Biogenic synthesis of silver nanoparticle from wasp nest soil fungus, Penicillium italicum and its analysis against multi drug resistance pathogens. (October 2018) - Nayak, B.K.; Nanda, A.; Prabhakar, V.
Abstract: The mortality rate has increased robustly due to the drug resistant microorganisms and is a major challenge before scientist. Since nature provides the clues to us to defend against unfavorable situation, the proposed study has focus on an insect-microbe symbiosis which plays a vital role for producing the natural product for an alternate source of antibiotic. In our present study we have isolated fungi Penicillium italicum from wasp nest soil and checked the symbiotic relation is more promising than the individual growth. Further the study was subjected to extracellular biosynthesis of silver nanoparticles. The biosynthesized nanoparticles were characterized by various techniques followed by antibacterial and antifungal activity against multi drug bacterial pathogens like Staphylococcus aureus, Vibrio parahaemolyticus, E. coli, Shewanella putrefaciens and fungal pathogen of Candida albicans . The silver nanoparticles were synthesized by adding silver nitrate to the culture extract of Penicillium italicum . The UV-Vis spectrophotometer showed the absorption peak at 419–421 nm and the Scanning Electron Microscopy showed the particle size of 33 nm. The Synthesized silver nanoparticles were found to have diverse antimicrobial activities against the pathogens at different pH. Antimicrobial assay of silver nanoparticles from P. italicum revealed that the synthesized nanoparticle had good effect at different levels to MDR pathogen of Staphylococcus aureus, Shewanella putrefaciens and fungal pathogen of Candida albicans . Synthesized nanoparticles from the fungi specially cultivated from the wasp nest soil has better antimicrobial activity against multi drug resistant pathogens MDRs and is reliable, ecofriendly economic to synthesizes the noble nanomaterials. Graphical abstract: Highlights: The mortality rate has increased robustly due to the drug resistant microorganisms and it is a major challenge before scientists. Insect-microbe symbiotic relationship has focused for producing the extracting the product naturally. Synthesized nanoparticles from the fungi specially cultivated from the wasp nest soil has better antimicrobial activity observed against multi drug resistant pathogens. Nanoparticles blend with antibiotics showed a promising material against MDRs to be used as noble nanomaterials.